Staying healthy abroad : a global traveler's guide - Sanford, Christopher (University of Washington Press, 2018)
Whether planning a long weekend in Mexico or an African safari, travelers need current and practical information on protecting their health in foreign countries. Staying Healthy Abroad gives straightforward and easy-to-follow recommendations for those traveling for pleasure, study, business, or volunteer work; for short- or long-term stays; and to destinations ranging from rural areas to large cities, in both developing and industrialized nations. Observing that risk is determined less by where you go than by what you do, physician and educator Christopher Sanford provides succinct overviews and commonsense advice on how to prevent communicable diseases, malaria and other mosquito-borne illnesses, and travelers' diarrhea; avoid traffic and water accidents; and evaluate post-trip symptoms; and addresses many other concerns. His emphasis is on ailments and injuries that travelers are most likely to encounter, because "if something occurs less frequently than one-in-a-million, it probably isn't going to happen to you." Staying Healthy Abroad also covers concerns unique to women, men, children, LGBTQ individuals, and travelers with chronic illnesses. International travel can be a business requirement, a study-abroad opportunity, an exciting adventure, or a quick getaway outside the normal routine. The majority of health and safety risks for travelers can be avoided with sensible pre-travel precautions, such as immunizations, and attention to safe behavior while away. From altitude sickness to Zika virus, the clear and concise information in Staying Healthy Abroad helps make global travel less stressful and more enjoyable.